2022
DOI: 10.3934/era.2022236
|View full text |Cite
|
Sign up to set email alerts
|

Transmission effect of extreme risks in China's financial sectors at major emergencies: Empirical study based on the GPD-CAViaR and TVP-SV-VAR approach

Abstract: <abstract> <p>Major emergencies cause massive financial risk and economic loss. In the context of major emergencies, we propose the GPD-CAViaR model to depict the extreme risks of financial sectors, and utilize the TVP-SV-VAR model to analyze their transmission effect. We find that (ⅰ) the securities sector has the highest extreme risks among the four financial sectors; (ⅱ) when major emergencies occur, the extreme risks of various financial sectors increase rapidly; (ⅲ) the transmission effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Other scholars have investigated the impact of major emergencies, such as Ukwuoma [5], Benifa [6], Asif [7], and Fazmiya [8], who analyzed the physical effects of major emergencies on humans from a medical perspective, using COVID-19 as an example. Mo et al [9] argued that major emergencies have both an emotional as impact as well as a huge economic impact. Cheng et al [10] found that secondary disasters of major emergencies can have an impact on international oil prices.…”
Section: Related Workmentioning
confidence: 99%
“…Other scholars have investigated the impact of major emergencies, such as Ukwuoma [5], Benifa [6], Asif [7], and Fazmiya [8], who analyzed the physical effects of major emergencies on humans from a medical perspective, using COVID-19 as an example. Mo et al [9] argued that major emergencies have both an emotional as impact as well as a huge economic impact. Cheng et al [10] found that secondary disasters of major emergencies can have an impact on international oil prices.…”
Section: Related Workmentioning
confidence: 99%